Customer Satisfaction in Retail Banking Services in Nepal - Subedi, Phul Prasad (PYC Nepal Journal of Management, 2019)
This research mainly focuses on analysing the factors affecting customer satisfaction in retail banking in Nepal. The study adopts descriptive and explorative research design to deal with the fundamental issues associated with various factors of customers’ satisfaction and retail banking. The study is based on questionnaire survey of 200 customers of 10 different “A” class financial institutions, i.e. commercial banks. Descriptive statistics, correlation coefficient and regression analysis have been applied to estimate the relationship between customer satisfaction as dependent variable and service quality variables as independent variables. The empirical evidences indicate that reliability, responsiveness, assurance and tangibles factors have positive and significant impact on customer satisfaction. It reveals that higher the level of responsiveness, reliability, assurance and tangibility higher would be the customer satisfaction.